2008
DOI: 10.1186/ar2408
|View full text |Cite
|
Sign up to set email alerts
|

Early atherosclerosis in systemic sclerosis and its relation to disease or traditional risk factors

Abstract: Introduction Several systemic autoimmune diseases are associated with an increased prevalence of atherosclerosis which could not be explained by traditional risk factors alone. In systemic sclerosis (SSc), microvascular abnormalities are well recognized. Previous studies have suggested an increased prevalence of macrovascular disease as well. We compared patients with SSc to healthy controls for signs of early atherosclerosis by measuring intima-media thickness (IMT) of the common carotid artery in relation to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
41
2
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 38 publications
4
41
2
1
Order By: Relevance
“…Although inflammation plays a very important role in all stages of atherosclerosis/thrombosis and is regarded as the main reason for increased CVD in autoimmune diseases (39,40), in SSc inflammation it is not as prominent and severe as in RA or SLE. The majority of the studies of CVD or atherosclerosis in SSc either did not evaluate acute-phase reactants or did not show any difference in the levels of ESR or CRP between SSc patients with and without CVD or atherosclerosis (3,9,11,38). Besides our study, the contribution of inflammation has been shown in only 1 recent study (16).…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Although inflammation plays a very important role in all stages of atherosclerosis/thrombosis and is regarded as the main reason for increased CVD in autoimmune diseases (39,40), in SSc inflammation it is not as prominent and severe as in RA or SLE. The majority of the studies of CVD or atherosclerosis in SSc either did not evaluate acute-phase reactants or did not show any difference in the levels of ESR or CRP between SSc patients with and without CVD or atherosclerosis (3,9,11,38). Besides our study, the contribution of inflammation has been shown in only 1 recent study (16).…”
Section: Discussioncontrasting
confidence: 49%
“…These surrogate markers of atherosclerosis have also been investigated in SSc. Although cIMT and carotid plaque prevalence were widely varied among different studies (9)(10)(11)(12), pooled data from meta-analyses and recent larger studies indicated that SSc patients had both a higher frequency of subclinical atherosclerosis and higher cIMT compared to HS (13,16,18). The discrepancies in the study results could be partially explained by differences in included patients and the sample sizes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although myocardial insufficiency in SSc has been attributed to microvascular disease (28) and imbalanced hemostasis (29) in earlier studies, coronary atherosclerosis has been increasingly revealed by conventional coronary angiography in SSc patients (13,14), concomitant with the significantly improved survival of these patients over the past decades (30). Other macrovascular diseases, such as peripheral vascular disease, have also been frequently reported in SSc patients (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…As postulated for other rheumatic diseases, coronary atherosclerosis may be related to the long-term effect of the underlying inflammation (4), which may not be adequately reflected by cross-sectional measurements of markers of inflammation or disease activity score. We postulated that endothelial dysfunction and inflammation were the key pathogenic mechanisms shared by atherosclerosis and SSc (31). Endothelial dysfunction has been well described in SSc patients, as evidenced by impaired flow-mediated dilation of the brachial artery on Doppler ultrasound scan (40,41) and elevated serum levels of markers of endothelial injury (42).…”
Section: Discussionmentioning
confidence: 99%